Stakeholders prioritization of climate information services (CIS) in the rice-based production systems of Mali - Dossou-Yovo, Elliott Ronald; Arouna, Aminou; Bryan, Elizabeth; Ringler, Claudia; Futakuchi, Koichi; Grosjean, Godefroy; Mujawamariya, Gaudiose; Benfica, Rui; Freed, Sarah; Rodrigue, Yossa (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
This study used a stakeholder prioritization framework to assess and rank locally suitable climate information services (CIS) and implementation suitability with key stakeholders: Center for Mechanized Agriculture, seed companies (Faso Kaba), Green Innovation Centers, National Institute for Rural Economy, NGOs (GIE-GNELENI, JMI), Niger Office, Syngenta Foundation for Sustainable Agriculture, Women Association and Youth Association. The prioritization was made in two steps for each of the four major rice production systems in Mali (irrigated lowland, rainfed lowland, rainfed upland, and submergence). The first step consisted of the review and evaluation of location-specific CIS based on their contribution to increasing farm productivity, reducing yield loss due to climatic risks, and reducing greenhouse gas emissions. The second step consisted of the evaluation of the implementation feasibility, gender inclusivity, readiness to scale, cost of implementation, and demand by the market. In all the four production systems, the overall CIS performance score was more determined by the ability of the CIS to increase resilience than to increase productivity, income and to enhance gender inclusivity. In the irrigated lowland, the CIS technologies with a high score include cropping calendar construction, cold occurrence and duration, flooding occurrence and duration, information on dam water level, pest and disease occurrence, and suitable area for rice cultivation. In the rainfed lowland, the CIS technologies with a high score include flooding occurrence and duration, suitable area for rice cultivation, onset and cessation of the rainy season, cropping calendar construction, and pest and disease occurrence. In the rainfed upland, the CIS technologies with a high score include onset and cessation of the rainy season, pest and disease occurrence, seasonal rainfall amount, cropping calendar construction, and drought occurrence and duration. In the submergence system, the CIS technologies with a high score include suitable area for rice cultivation, pest and disease occurrence, flooding occurrence and duration, and cropping calendar construction. The framework used in this study provides a decision support tool for policymaking in adaptation and mitigation activities in the rice-based sector at the local level.